Relación entre la metodología para la enseñanza y el aprendizaje de la convivencia en los estudiantes del 5to grado de secundaria de la I.E Manuel Segundo del Águila - Cárdenas Cárdenas, Elena (2014)
Human being throughout the historical evolution has been shaped as a social being par excellence. From its earliest stages could not break away from his fellows and as efficiently evolve to the present. lnstead, he had to be around your group how ensured its survival and improved their progress. This natural source development has made the need to interrelate become a basic factor of lite in groups and events which becomes increasingly efficient as the social context over time acquires greater complexity while no longer enough to stop the acquisition of skills inherent to the simple everyday bustle. Currently let this happen is to give way to indifference and chaos. Social skills training is therefore prevent serious personal and social futures (Monjas, 1997). lt involves learning and practice of promoting values such as solidarity, peace, tolerance, dialogue, justice, individual and social responsibility, much needed in present times. Despite its apparent complexity, coexistence and social skill set, do not present much difficulty for learning, since as noted Morris (1997), citing indicating social learning theory that this is done by means of observing a model or instruction, without the learner having experience first hand, at least as a starting point. Meanwhile Bandura (1977) adds to this concept the idea that the experiences observed in the environment become symbolic representations that serve as guidelines for action. Given that different social spaces to school have not implemented a system of social learning and that it is determined by the simple interactive spontaneity or generic rules that society has historically been put rules, our study finds that this variable must be built based on learning procedures associated primarily a monitoring methodology enriched able to shape experiences in human behavior according to the canons that humanity requires today, to make our global community a dignified and suitable to live harmonically. The scientific concern that motivated us was to find a possible link between the methodology implemented and enforced by teachers to guide the teaching of social interaction skills to students in the fifth grade of secondary school space within the institution educational Manuel Segundo Del Aguila Velasquez of the district Rioja. Our expectation, based on relevant theory, was to find a positive relationship between these two variables. lf we consider that in the school who structured learning experiences are the teachers and those who are students vivencian, measurement methodology for teaching coexistence defined by teachers' responses to a questionnaire about the closed based strategies used both the group and individuality while learning, expressed as a set of social skills was measured through a Likert attitudinal scale, covering five dimensions of the construct coexistence. By relating the methodology used by teachers for teaching learning to live with this variable was found to link favorable trend with a high degree of significance. In this environment you may find the learning climate is also favorable what is being achieved, as noted by Garcia and Lopez (1988), thanks to the inclusion of evaluative character elements of the social dimension in the training process of students. As stated, over the interpretation of the findings of our research, the social nature of the human being as an entity has been configured with a tendency to group living, that's why people always look for a favorable environment for the efficient conduct of their daily activities such. as learning as demonstrated by the CASEL (2008), even experimentally, where the teaching strategies, interactive play an important role. Work by Grineski (1996) allows us to dispel doubts about the multidimensional impact that generates social learning in humans, benefiting not only the physiological, but also the emotional, basis for the incorporation and exercise their skills coexistence.